2010
DOI: 10.3109/02688690903572095
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of spontaneous subarachnoid haemorrhage — A ruptured aneurysm of a basilar perforator artery

Abstract: A 51-year-old gentleman with no significant past medical history presented with a WFNS grade 1 subarachnoid haemorrhage. Initial angiographic investigations revealed no cause, but repeat tests showed a small basilar perforator aneurysm. Following a failed attempt at endovascular treatment, a craniotomy and excision of the aneurysm was performed. Post-operatively the patient made a good recovery. This case highlights the importance of delayed repeat catheter angiography in selected patients with suspicious init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 4 publications
(1 reference statement)
1
42
0
Order By: Relevance
“…Since first described by Ghogawala et al in 1996, 17 cases have been reported. [2][3][4][5][6][8][9][10]12 Since the beginning of 2012, at our institution we have encountered 3 ruptured perforator aneurysms of the posterior circulation. Those cases are reported in detail below.…”
Section: ©Aans 2014mentioning
confidence: 99%
See 3 more Smart Citations
“…Since first described by Ghogawala et al in 1996, 17 cases have been reported. [2][3][4][5][6][8][9][10]12 Since the beginning of 2012, at our institution we have encountered 3 ruptured perforator aneurysms of the posterior circulation. Those cases are reported in detail below.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Just as in 1 of the cases presented in this paper, basilar perforators can be inaccessible to catheterization 3,6,8 due to their small diameter, distal localization, and low blood flow. Surgery is often chosen as the first line of treatment, [4][5][6]8,12 including direct clipping, clipping of the parent vessel of the aneurysm, excision, trapping, wrapping, and coagulation. Endovascular techniques consist of coiling, stenting, or embolization.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, re-rupture occurred in one of seven cases in our review that was not treated early [5]. Oft-seen proximal clip occlusion or trapping approach was employed in treating these aneurysms [5,6], but the vessel was small, diseased, and often less collateralized by frequently seen anastomoses. In addition, given the extremely fragile wall of aneurysm, the surgical management can be complicated and risky; these aneurysms are candidates for endovascular therapy.…”
Section: Discussionmentioning
confidence: 99%